A rapid multidimensional GC–flame-ionization detector method for determination of fatty acid methyl esters. (February 2014) - Xu, Yong-Jiang; Zhang, Jianbing
Background: Fatty acids play important roles in the pathogenesis of many diseases. In order to investigate a wide spectrum of fatty acids in biological matrix, we developed an approach for quantitative analysis of fatty acids based on a heart-cutting 2D gas chromatographic-flame ionization detector system.Results: This system uses a Dean Switch interface between the primary polar and secondary nonpolar capillary column. Most of the standards were separated by the primary column. Unresolved components are selectively transferred to the secondary column, where they are completely separated. This method was further evaluated using plasma obtained from 11 healthy and 11 chronic coronary artery disease patients.Conclusion: Our results prove that this approach is sensitive, precise and specific, capable of measuring 37 specific fatty acids. It indicates that this approach offers a reliable and sensitive technical platform for comprehensive quantification of fatty acids.